(untitled) (Historia, 2021)
Industrialisation in South Africa : an historical debate? Historians have not given much attention to industrialisation as an economic phenomenon. The majority of historical publications deal with the social and political implications of the phenomenon. This article analyses the work of economic historians initially, then the publications of economist historians. Agreement exists on the cost of industrial protectionism, as well as the initial necessity thereof to stimulate economic growth. Economists intensively debated the govermnent's decentralisation programme and questioned the political motivation for the policy. The revisionist historians' publications basically address the idea that political policies were used to ensure capitalist development. The author finds that very little real debate has taken place between the first two groups of writers and the revisionist historians. Industrialisasie as 'n ekonomiese verskynsel het min aandag van historici ontvang. Die meeste publikasies van historici handel oor die sosiale en politieke implikasies van die verskynsel. Hierdie artikel ontleed die werk van ekonomiese historici in die eerste plek, dan die werk van ekonome en daarna revisionistiese historici. Daar is groot ooreenstemming oor die koste van aanvanklike industriële proteksionisme, asook die aanvanklike nut daarvan ten einde ekonomiese groei te stimuleer. Ekonome bet indringend gedebateer oor die owerheid se desentralisasieprogram en veral die politieke rasionaal daaragter bevraagteken. Die revisionistiese publikasies oor industrialisasie handel hoofsaaklik oor die idee dat politieke beleidsrigtings geïmplementeer is om kapitalistiese ekonomiese ontwikkeling te verseker. Die skrywer beweer dat min werklike debat tussen die eerste groepe skrywers oor industrialisasie en laasgenoemde revisionistiese historici plaasvind.